An exciting twenty-year journey exploring porphyrinoid-based photo- and electro-active systems - Bottari, Giovanni; de la Torre, Gema; Guldi, Dirk Michael; Torres, Tomás (Coordination Chemistry Reviews, 2021)
This review highlights the combined effort of the Torres and Guldi groups in the preparation and study of porphyrinoid-based photo- and electro-active systems. The perfect synergy between the deep knowledge on the chemistry of porphyrinoids and advanced carbon allotropes possessed by the Spanish team, and the profound expertise in the advanced photophysical characterization and photon- and charge-management held by the German group represents the real asset of this transnational collaboration. Along the last twenty years, the two groups have developed a plethora of electron donor–acceptor architectures based mainly on phthalocyanines and subphthalocyanines, but also porphyrins and other porphyrinoids, connected, either covalently or through supramolecular interactions, to several electroactive units such as advanced carbon allotropes, that is, fullerenes, carbon nanotubes, and graphene, among others. Important guidelines relating the structural and electronic features of such photo- and electro-active species with physical aspects such as the dynamics of charge separation, charge transport, charge shift, and charge recombination processes have been obtained. This knowledge has resulted crucial for the implementation of many of these systems into applied research fields such as optoelectronics, solar energy conversion, and biomedicine.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Advanced carbon allotropes; Electron donor–acceptor systems; Energy conversion; Phthalocyanines; Subphthalocyanines